2018
DOI: 10.3389/fphys.2018.00913
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Impairment of Neurovascular and Neurometabolic Coupling in the Hippocampus

Abstract: Neurovascular and neurometabolic coupling are critical and complex processes underlying brain function. Perturbations in the regulation of these processes are, likely, early dysfunctional alterations in pathological brain aging and age-related neurodegeneration. Evidences support the role of nitric oxide (•NO) as a key messenger both in neurovascular coupling, by signaling from neurons to blood vessels, and in neurometabolic coupling, by modulating O2 utilization by mitochondria. In the present study, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…In certain mitochondrial encephalopathies and lactic acidosis, uncoupling of rCBF and CMRglu occurs ( 54 , 55 ), indicating that alterations in oxidative stress pathways may be relevant to our current observation in schizophrenia. In experimental models, neurovascular coupling is impaired in young rodents when redox imbalance is created by increasing intracellular generation of superoxide radicals ( 56 ). Glutathione, a major intracellular antioxidant that protects neuroglia from oxidative stress by disposing peroxides, is notably reduced in schizophrenia particularly in the medial prefrontal cortex ( 57 ), especially in patients with poor outcomes ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…In certain mitochondrial encephalopathies and lactic acidosis, uncoupling of rCBF and CMRglu occurs ( 54 , 55 ), indicating that alterations in oxidative stress pathways may be relevant to our current observation in schizophrenia. In experimental models, neurovascular coupling is impaired in young rodents when redox imbalance is created by increasing intracellular generation of superoxide radicals ( 56 ). Glutathione, a major intracellular antioxidant that protects neuroglia from oxidative stress by disposing peroxides, is notably reduced in schizophrenia particularly in the medial prefrontal cortex ( 57 ), especially in patients with poor outcomes ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CEC dysfunction can trigger BBB damage, which induces inflammation and neurotoxicity. Later, neuronal impairments or death occurs, eventually leading to cognitive dysfunctions [54,56,59].…”
Section: Vad and Neurovascular Dysfunction (Cec Dysfunction And Nervous Impairment)mentioning
confidence: 99%
“…Furthermore, ONOO − can oxidize soluble guanylate cyclase (sGC) and reduce its reactivity to NO. It reduces the production of cGMP, preventing cGMP-dependent kinase from being activated and failing to carry out vasodilation [59,71,94,111,112]. Additionally, recent studies have observed that supplementation with BH 4 can only partially restore the functions of eNOS, suggesting that there is another potential mechanism of eNOS uncoupling.…”
Section: Enos Uncouplingmentioning
confidence: 99%
“…The close association of CECs and neural cells allows the signals by CEC damage to be transduced to the brain [e.g., the impaired NO function alters the synaptic plasticity ( Blackshaw et al, 2003 )]. Therefore, signal disturbances of NVU might underlie the nerve injury, apoptosis and neurological dysfunction ( Lourenco et al, 2018 ; Maiuolo et al, 2018 ). Thus, CECs are not only the primary components of BBB structurally but also the key link of NVU activities functionally.…”
Section: Structural and Functional Characteristics Of Cecsmentioning
confidence: 99%